Mechanisms of antidepressant resistance - El Hage, Wissam; Leman, Samuel; Camus, Vincent; Belzung, Catherine (Frontiers in Pharmacology, 2013)
Depression is one of the most frequent and severe mental disorder. Since the discovery of antidepressant properties of the imipramine and then after of other tricyclic compounds, several classes of psychotropic drugs have shown be effective in treating major depressive disorder. However, there is a wide range of variability in response to antidepressants that might lead to non response or partial response or in increased rate of relapse or recurrence. The mechanisms of response to antidepressant therapy are poorly understood, and few biomarkers are available than can predict response to pharmacotherapy. Here, we will first review markers that can be used to predict response to pharmacotherapy, such as markers of drug metabolism or blood-brain barrier function, the activity of specific brain areas or neurotransmitter systems, hormonal dysregulations or plasticity, and related molecular targets. We will describe both clinical and preclinical studies and describe factors that might affect the expression of these markers, including environmental or genetic factors and comorbidities. This information will permit us to suggest practical recommendations and innovative treatment strategies to improve therapeutic outcomes.